Researching achievement and inclusion to improve the educational experiences and outcomes of all learners - Lani FLORIAN; Martyn ROUSE; Kristine BLACK-HAWKINS (Ediciones Universidad de Salamanca, 2011)
This paper considers some of the key issues that must be taken into account when conducting research on inclusive education in an era of standards based reform. It challenges the widely held assumption that high levels of educational inclusion are incompatible with high levels of academic achievement in schools and presents the Framework for Participation, a research tool developed by the authors, which supports practitioners (and other researchers) who wish to examine the development of inclusive practice in their own schools.